2D Numerical analysis of micro-cracks - Elisaveta Doncheva, Gjorgji Adziev (Scientific association for development and affirmation of new technologies, 2015)
In this paper, 2D numerical models are developed in order to investigate the micro-cracks initiation caused by the persistent slip bands formation inside the grains of polycrystalline materials. The structure is artificially generated and should be similar to the grain structure present in real materials. Considering the crystallographic orientation of each grain through which the distribution of stress and deformation can be observed, initiated micro-cracks tend to propagate in certain manner. The results from the analysis are describing the impact of grains density, shape and orientation on micro-cracks propagation, theoretically and numerically. The results obtained are compared with various experiments and conclusions by different authors and are presented in order to get a good overview of the problem and to propose a different approach in representing the cracks numerically.
Keywords: Micro crack; Crystal grains; Voronoi tessellation; Persistent slip bands; Shear stress